The mixed spin-1/2 and spin-1 Ising system on a two-layer Bethe lattice - KPLE, JOËL; AVOSSEVOU, GABRIEL YVES HUGUES; HONTINFINDE, FÉLIX (My University, 2013)
Two layered magnetic Bethe lattice with varying coordination number q is introduced and numerically stud-ied via exact recursion relations within a pairwise approach. The system is influenced by competing in- terlayer and intralayer nearest-neighbour (NN) coupling interactions and also by the crystal and external magnetic fields. Cases where both layers are ferromagnetic or one is ferro and the other antiferromagnetic are considered. System configurations’ energy calculations are used to devise some ground state phase diagrams that have proven useful for the investigation of the very low temperature behaviour of the model. Analysis of the thermal behaviours of the total magnetization within the model parameters’ space yield interesting phase diagrams which display fascinating properties, in particular the presence of tricritical points. Increasing negative values of the crystal field strength stabilizes the disordered paramagnetic phase and sometimes gives rise to wavy transition lines.
Keywords: bilayer Bethe lattice; mixed spin-1/2 and spin-1 model; ground states; recursion relations; tricritical and; compensation points